Distributed and Parallel Databases Journal (DAPD) - (:unkn) unknown (My University, 2026)
Lead Editor of Special Issue “Self-managing and Hardware-optimizing Database systems 2020” for Distributed and Parallel Databases Journal (DAPD). https://link.springer.com/collections/fgeacfdgeh